Angiogenesis in peripheral arterial disease. (April 2018) - Inampudi, Chakradhari; Akintoye, Emmanuel; Ando, Tomo; Briasoulis, Alexandros
Highlights: The goal of angiogenesis in PAD is formation of collateral circulation. It may be particularly useful for patients no deemed candidates for revascularization. Angiogenic growth factors don't improve ulcer healing and amputation rates. Intra-arterial or intra-muscular injection of stem cells did not improve outcomes. Abstract : Peripheral arterial disease (PAD) refers to narrowing of the peripheral arteries and atherosclerosis is the most important cause. In patients with PAD, revascularization is the preferred therapeutic strategy; nonetheless several patients are not deemed candidates for it due to advanced disease or several comorbidities. The main target of therapeutic angiogenesis is to promote development of new arterial vessels and improve perfusion of ischemic tissue. Angiogenic growth factors such as vascular endothelial growth factor (VEGF), fibroblast growth factor (FGF), hepatocyte growth factor (HGF), administered intramuscularly or intra-arterially, have been shown to promote angiogenesis and development of collateral vasculature in preclinical studies. However, clinical studies failed to confirm their efficacy in ulcer healing and prevention of amputation, among patients with claudication or critical limb ischemia (CLI). Autologous progenitor cell therapy with bone marrow or adipose-derived progenitor cells administered intra-arterially or intra-muscularly, was shown to improve claudication symptoms and ankle–brachial index in small studies. However, subsequent randomized controlled studies did not demonstrate any beneficial effects of stem cell therapy on amputation rates and survival. Although, therapeutic angiogenesis remains an area of interest in PAD with several ongoing studies of investigational therapies, so far the use of these strategies in clinical practice has not been successful.